Mood and Modality in the song “Reckless” by Madison Beer within Semantics - Rotua Sinta Marito Pakpahan; Bernieke Anggita Ristia Damanik (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Mood and modality are important aspects of semantic studies because they express attitudes, emotions, certainty, obligation, and intention through language. The aims of this research are to identify and describe the types of mood and modality found in the song